PKSâ Democratic Experiences in Recruiting Members and Leaders - Nurdin, Ahmad Ali (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2011)
This paper focuses on the views of democracy and the implementation of democratic rules in real politics by the Islamic political party that has a democracy platform in Indonesia, Partai Keadilan Sejahtera (PKS). I examine PKS views on the relationship between Islam and democracy and its manner of recruiting members and leaders to show that this Islamic political party is not a threat to democracy at all. PKS believes that democracy goes to the roots of Islam and the Indonesian context in which they exist; and that it is a good political tool for an Islamic party like PKS to achieve its political goals. Taking the process of recruitment of members and leaders of PKS as examples, the paper also shows that the commitment of PKS to strengthening democracy in Indonesia could be seen in their process of recruiting leaders. PKS has practiced democratic rules in their internal party activities, particularly in the way they used to recruit their members who would be nominated as parliamentary members and how they choose their own leaders. However, it is necessary to note that in terms of member recruitment and expanding the cadres of the party, the PKS seems to have a special strategy; that is, encouraging their cadres to have big families.[Artikel mengulas pandangan Partai Keadilan Sejahtera (PKS) mengenai demokrasi dan implementasi nilai-nilai demokrasi dalam kehidupan politik. Dalam artikel ini, relasi Islam dan demokrasi serta metode PKS dalam merekrut anggota dan pemimpin partai akan dibahas. PKS sama sekali bukanlah ancaman bagi demokrasi. PKS percaya bahwa prinsip demokrasidapat ditemukan dalam Islam dan konteks Indonesia. Bagi PKS, demokrasi membuka ruang kesempatan bagi partai politik Islam untuk mencapai tujuan politiknya. Selain itu, artikel ini juga mengulas proses rekrutmen anggota dan pemimpin partai. Rekrutmen petinggi PKS memperlihatkan komitmen PKS terhadap penguatan demokrasi di Indonesia. PKS sudah mempraktekkan prinsip demokrasi dalam tubuh partai, utamanya dalam menentukan kandidat anggota parlemen dan dalam memilih pemimpin. Yang perlu diperhatikan adalah tampaknya PKS menerapkan pola rekrutmen dan ekspansi anggota partai yang unik, yaitu dengan mendorong kader-kader PKS untuk mememiliki banyak anak.]